Preparation method and application of novel tin dioxide / tin disulfide@carbon composite negative electrode material

CN117334881BActive Publication Date: 2026-10-09YANGTZE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311530692.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-16
Publication Date
2026-10-09
Estimated Expiration
2043-11-16

AI Technical Summary

Technical Problem

但二者在充放电过程中均涉及相变和合金反应,不可避免产生体积膨胀效应,使得材料结构遭到破坏,容量急剧衰退,体积膨胀和低导电性阻碍了锡基负极材料的商业化

Benefits of technology

[0022](1) The preparation method of the present invention first dissolves tin salt and additives in a mixed solvent. Part of the additives are used as complexing agents to form very fine coordination compound clusters, and the other part can be used as hydrolysis and alcoholysis catalysts. Then, conductive carbon and sulfur source are introduced under ultrasonic assistance to attract tin ions. The adsorbed growth units are confined in extremely small coordination compound clusters. During the hydrothermal process, nucleation and growth occur at the crystal interface through dehydroxylation and sulfidation reactions to form heterojunction quantum dots, which are uniformly dispersed on conductive carbon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117334881B_ABST
    Figure CN117334881B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery material preparation, and particularly discloses a preparation method of a novel SnO2 / SnS2@carbon composite negative electrode material and application thereof. A tin source and an additive are dissolved in a mixed solvent of alcohol and deionized water to obtain a tin quantum dot precursor solution; under ultrasonic conditions, a carbon source and a sulfur source are sequentially added, and a one-pot hydrothermal reaction is performed to obtain a composite material of conductive carbon loaded with SnO2 / SnS2 composite quantum dots. The preparation method is simple, does not require sintering, and has good repeatability. The prepared SnO2 / SnS2 heterojunction quantum dots are uniformly dispersed in the conductive carbon. The prepared negative electrode material has a capacity of 815.8 mAh / g at a current density of 10.0 A / g as a lithium ion battery negative electrode material, and has a capacity of 260.7 mAh / g at a current density of 5.0 A / g as a sodium ion battery negative electrode material, and has good battery performance and wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material preparation technology, specifically relating to a method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material and its application. Background Technology

[0002] Lithium-ion batteries possess advantages such as high energy density, long lifespan, no memory effect, and environmental friendliness, making them crucial in portable devices and new energy vehicles. Sodium-ion batteries, while sharing a similar working principle with lithium-ion batteries, benefit from the low cost, uniform distribution, and abundant reserves of sodium resources, which can meet large-scale energy storage demands. Therefore, sodium-ion batteries can serve as an important supplement to lithium-ion batteries in this field. To support the upgrading of consumer electronics and meet the needs of high-power electrical devices and energy storage equipment, developing high-capacity, high-rate, and low-cost battery materials has become a key research focus.

[0003] Tin-based materials have attracted widespread attention from researchers due to their advantages such as high theoretical specific capacity, low cost, simple synthesis methods, and environmental friendliness, making them one of the most promising anode materials for lithium-ion and sodium-ion batteries. Among them, high-capacity tin dioxide (SnO2, with a theoretical lithium storage capacity of 1494 mAh / g and a theoretical sodium storage capacity of 1398 mAh / g) and tin disulfide (SnS2, with a theoretical lithium storage capacity of 1231 mAh / g and a theoretical sodium storage capacity of 1136 mAh / g) are strong contenders for next-generation anode materials. However, both involve phase transitions and alloying reactions during charge and discharge, inevitably resulting in volume expansion. This damages the material structure, leading to a sharp decline in capacity. Volume expansion and low conductivity hinder the commercialization of tin-based anode materials.

[0004] To optimize the cycle performance and rate performance of tin-based materials such as tin dioxide and tin disulfide during charge-discharge processes, combining them with carbon materials and constructing nanostructures is an effective method. Constructing nanostructures and further reducing them to quantum dots can effectively reduce the absolute volume change of the material while improving its structural stability. The introduction of carbon materials not only restricts the size of the material but also improves its conductivity, thereby enhancing its electrochemical performance. Tin-based quantum dot composite materials prepared by combining tin-based quantum dot materials with carbon materials hold promise for solving problems such as structural collapse and rapid capacity decay. Therefore, how to prepare smaller tin-based nanoparticles and uniformly disperse them in carbon materials is a key direction in the research of tin-based anode materials and is of great significance to the development of tin-based anode materials. Summary of the Invention

[0005] This invention aims to provide a method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material and its application. This invention nanoscales tin-based materials by constructing tin dioxide / tin disulfide heterojunction quantum dots, and further disperses and confines the quantum dots using the electrostatic attraction of conductive carbon under ultrasonic assistance. This material exhibits excellent electrochemical performance as an anode material for lithium-ion and sodium-ion batteries.

[0006] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution:

[0007] A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, the specific operation of which is as follows:

[0008] Step (1): Dissolve the tin source and additives in a mixed solvent of organic alcohol and deionized water (preferably a mixed solvent of anhydrous ethanol and deionized water with a volume ratio of 1:1), and stir under controlled temperature until uniformly dispersed to form a colloidal solution of tin quantum dot precursor.

[0009] Step (2): Add the carbon source and sulfur source to the precursor solution obtained in step (1) and stir continuously for 6 to 30 hours. During the stirring process, add ultrasonic assistance to form a precursor reaction solution.

[0010] Step (3): The precursor reaction solution obtained in step (2) is loaded into a high-pressure reactor and subjected to hydrothermal reaction at 120-300℃ for 6-36 hours. After the reaction is completed, the resulting solid-liquid mixture is centrifuged, washed and dried to obtain the novel tin dioxide / tin disulfide@carbon composite anode material.

[0011] The carbon source is a carbon material with a negatively charged surface.

[0012] As a preferred embodiment, in step (2), the specific conditions for ultrasonic assistance are: ultrasonication is performed at intervals while stirring, each time for 0.5 hours, and the total ultrasonic time is 2 to 3 hours. More preferably, the ultrasonic conditions are: frequency of 40KHz and power of 700W.

[0013] As a preferred embodiment, in step (1), the tin source is SnCl2, SnCl4, SnSO4, Na2SnO3, K2SnO3, Sn(CH3COO)2, SnC2O4, C 16 H 30 O4Sn, C 12 H 27 The additive is one or more of the following: N2H4·H2O, NH3·H2O, NaOH, NaHCO3, Na2CO3, KOH, KHCO3, K2CO3, C3H8O3, EG, VA, IPA, PEG, PVA, and the molar ratio of the additive to the tin source is (2-8):1.

[0014] As a preferred embodiment, in step (1), the molar concentration of the tin source in the tin quantum dot precursor colloidal solution is 6–24 mmol / L, the stirring temperature is 5–40℃ (preferably 25℃), and the stirring and dispersion time is 10–30 h.

[0015] As a preferred embodiment, in step (2), the carbon source is one or more of the following: carbon nanotubes with negative surface charge, graphene, porous carbon, anionic polymers, anionic polymer monomers, anionic polymer pyrolytic carbon, biochar, and activated carbon (preferably one or more of graphene, carbon nanotubes with negative surface charge, polyaniline, polypyrrole, and biochar; when graphene is selected, it is used in the form of a dispersion); the sulfur source is one or more of the following: thiourea, L-cysteine, sodium thiosulfate, sodium sulfide, ammonium thiocyanate, thioacetamide, ammonium sulfide, sodium sulfide, potassium sulfide, potassium thiocyanate, and sodium thiocyanate.

[0016] As a preferred embodiment, the mass ratio of the carbon source to the tin source is 1:(1-20), and in step (2), the molar ratio of the sulfur source to the tin source is (0.5-4):1.

[0017] As a preferred embodiment, in step (3), the hydrothermal reaction is carried out at a temperature of 150-200°C and a reaction time of 20-36 hours.

[0018] As a preferred option, in step (3), the drying method is selected according to the actual situation of the carbon source (freeze drying, vacuum drying, forced air drying, etc. can be selected, and freeze drying is preferred when the carbon source is graphene and carbon nanotubes).

[0019] Furthermore, this invention also provides the application of the novel tin dioxide / tin disulfide@carbon composite anode material obtained by the above preparation method in the preparation of battery anode materials.

[0020] As a preferred embodiment, the battery anode material is a lithium-ion battery anode material, a sodium-ion battery anode material, a potassium-ion battery anode material, or a lithium / sodium-sulfur battery anode material.

[0021] Compared with the prior art, the present invention has the following outstanding features and beneficial effects:

[0022] (1) The preparation method of the present invention first dissolves tin salt and additives in a mixed solvent. Part of the additives are used as complexing agents to form very fine coordination compound clusters, and the other part can be used as hydrolysis and alcoholysis catalysts. Then, conductive carbon and sulfur source are introduced under ultrasonic assistance to attract tin ions. The adsorbed growth units are confined in extremely small coordination compound clusters. During the hydrothermal process, nucleation and growth occur at the crystal interface through dehydroxylation and sulfidation reactions to form heterojunction quantum dots, which are uniformly dispersed on conductive carbon.

[0023] (2) The solvent selected in this invention is a mixture of water and ethanol, which is used for hydrolysis and alcoholysis respectively. The coordination compounds generated from the two parts form a heterojunction intermediate cluster. The selection of carbon source is to select a carbon source with a negative charge, such as a conductive polymer, a polymer with hydroxyl groups or other anionic polymers. The selection of the above carbon source can utilize its electrostatic attraction to disperse and confine.

[0024] (3) Ultrasonic assistance is used when introducing the carbon source to limit nucleation and form smaller quantum dots. In the prior art, sintering is carried out after hydrothermal treatment to make the heterojunction material more stable. However, the negatively charged carbon source and ultrasonic-assisted electrostatic attraction method used in this application to prepare the precursor solution can form a stable heterojunction material well after hydrothermal treatment. No further sintering is required after hydrothermal treatment. The negative electrode material prepared by the method of this invention adopts a one-step hydrothermal method, which does not require subsequent calcination or sintering processes. It has low energy consumption, high repeatability, and is easy to achieve large-scale production.

[0025] (4) The novel tin dioxide / tin disulfide@carbon composite anode material prepared by the method of the present invention has excellent electrochemical performance. As a lithium-ion battery anode material, its capacity can reach 815.8 mAh / g at a current density of 10.0 A / g; as a sodium-ion battery anode material, its capacity can reach 260.7 mAh / g at a current density of 5.0 A / g. It has certain application prospects in the field of secondary batteries. Attached Figure Description

[0026] Figure 1 This is the XRD pattern of the novel tin dioxide / tin disulfide@carbon composite anode material obtained in Example 1 of this invention;

[0027] Figure 2 This is a TEM image of the novel tin dioxide / tin disulfide@carbon composite anode material obtained in Example 1 of this invention;

[0028] Figure 3 This is a cycling diagram of the novel tin dioxide / tin disulfide@carbon composite anode material obtained in Example 1 of the present invention assembled with a lithium metal sheet into a half-cell.

[0029] Figure 4This is a cycle diagram of the novel tin dioxide / tin disulfide@carbon composite negative electrode material obtained in Example 1 of the present invention assembled with a sodium metal sheet into a half cell;

[0030] Figure 5 This is a rate capability diagram of a half-cell assembled with a lithium metal sheet using the novel tin dioxide / tin disulfide@carbon composite anode material obtained in Example 1 of this invention.

[0031] Figure 6 This is a rate curve of a half-cell assembled with a sodium metal sheet using the novel tin dioxide / tin disulfide@carbon composite anode material obtained in Example 1 of this invention. Detailed Implementation

[0032] To better understand the present invention, a detailed description will be provided below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of protection of the present invention.

[0033] In the following embodiments, the ultrasound conditions are: frequency of 40KHz and power of 700W.

[0034] Example 1: A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0035] Step (1): Measure 1.00 mmol SnCl2 and 120 μL hydrazine hydrate (>98%, the same below), dissolve them in a mixed solvent of 100 mL anhydrous ethanol and deionized water (the volume ratio of water to anhydrous ethanol is 1:1), and stir magnetically for 15 h at room temperature (25℃, the same below) to form a homogeneous precursor colloidal solution.

[0036] Step (2): Measure 4.5 mL of graphene dispersion (obtained by dispersing commercial graphene in deionized water with a concentration of 5 mg / mL) and 3.00 mmol of thiourea and add them sequentially to the precursor colloidal solution obtained in step (1). Continue to stir magnetically for 12 h until the solution changes from a brown solution to a black transparent solution. During the stirring process, sonicate every 1 h in the early stage, with each sonication lasting 0.5 h, for a total of 3 h, to form a stable precursor reaction solution (in this invention, the stability criterion is that the solution does not show obvious sedimentation or suspension after standing for 1 h, the same below).

[0037] Step (3): 105 mL of the precursor reaction solution obtained in step (2) was loaded into a high-pressure reactor (the volume of the polytetrafluoroethylene liner was 150 mL, the same below) and subjected to a hydrothermal reaction at a temperature of 150 °C for 20 h. The solid-liquid mixture obtained after the hydrothermal reaction was centrifuged, washed, and freeze-dried (freezing temperature was -52 °C for 72 h) to obtain the novel tin dioxide / tin disulfide@carbon composite anode material.

[0038] Figure 1-2 The XRD and TEM spectra of the composite anode material are shown below. Figure 1 Analysis shows that the product obtained in this embodiment corresponds well with the standard cards for SnO2 (JCPDS#77-0447) and SnS2 (JCPDS#83-1715). According to literature reports, the particle size range of quantum dots is 2–20 nm. The exciton Bohr radius of tin dioxide is 2.7 nm, and that of tin disulfide is 7.0 nm. When the particle size is smaller than the exciton Bohr radius, a quantum confinement effect occurs. Combined with… Figure 2 Analysis shows that the diameters of tin dioxide and tin disulfide particles in the material obtained in this embodiment are both 2.5–3.2 nm, and a heterojunction interface is formed between the crystals, indicating that tin dioxide / tin disulfide heterojunction quantum dots were successfully synthesized and are uniformly distributed on the graphene sheets.

[0039] The novel tin dioxide / tin disulfide@carbon composite negative electrode material prepared in this example was used as the active material for the working electrode to prepare electrode materials. The materials were then assembled into coin cells (lithium-ion batteries and sodium-ion batteries) for electrochemical performance testing.

[0040] Electrode materials were prepared by coating a slurry obtained by mixing active material, carbon black, and polyvinylidene fluoride in a mass ratio of 8:1:1 onto a copper foil current collector, drying the slurry, and then punching the electrode. The loading of the active material on the copper foil current collector was 1.2 mg / cm³. 2 .

[0041] When assembling lithium-ion batteries, lithium metal sheets are selected as the counter electrode, the electrolyte solute is 1 mol / L LiPF6, and the electrolyte solvent is ethylene carbonate, dimethyl carbonate, and diethyl carbonate (the volume ratio of ethylene carbonate, dimethyl carbonate, and diethyl carbonate is 1:1:1), with a polypropylene separator. When assembling sodium-ion batteries, sodium metal sheets are selected as the counter electrode, the electrolyte solute is 1 mol / L NaClO4, and the electrolyte solvent is dimethyl carbonate and diethyl carbonate (the volume ratio of dimethyl carbonate and diethyl carbonate is 1:1), with a glass fiber separator. Both are assembled into 2025 button cells.

[0042] Figure 3 The cycle performance curve of the lithium-ion battery assembled from the negative electrode material in this embodiment is shown. The current density is set to 0.1A / g. The test results show that after 100 cycles, the discharge specific capacity can reach 1667.9mAh / g.

[0043] Figure 4 The cycle performance curve of the sodium-ion battery assembled with the negative electrode material in this embodiment is shown. The current density is set to 0.1A / g. The test results show that after 100 cycles, the discharge specific capacity can reach 534.4mAh / g.

[0044] Figure 5 The rate performance curve of the lithium-ion battery assembled from the negative electrode material in this embodiment is shown. The current densities were set to 0.2, 0.5, 1.0, 2.0, 5.0, 10.0, and 0.2 A / g. The test results show that at a high rate of 10.0 A / g, its discharge specific capacity is still 815.8 mAh / g. When the current density is restored to 0.2 A / g, its discharge specific capacity is 1626.1 mAh / g.

[0045] Figure 6 The rate performance curve of the sodium-ion battery assembled with the negative electrode material in this embodiment is shown. The current densities were set to 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, and 0.1 A / g. The test results show that at a high rate of 5.0 A / g, its discharge specific capacity is still 260.7 mAh / g. When the current density is restored to 0.1 A / g, its discharge specific capacity is 517.9 mAh / g.

[0046] Example 2: A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0047] Step (1): Measure 1.50 mmol SnCl4 and 180 μL hydrazine hydrate, dissolve them in 100 mL of a mixture of anhydrous ethanol and deionized water (water and anhydrous ethanol volume ratio of 1:1), stir at room temperature for 20 h to form a homogeneous precursor colloidal solution.

[0048] Step (2): Weigh 39 mg of activated multi-walled carbon nanotubes (the commercially available multi-walled carbon nanotubes were activated before use. The activation reagent was concentrated nitric acid, the temperature was 120℃, and the activation time was 3 h. The specific activation method was: put the commercial multi-walled carbon nanotubes into 68% concentrated nitric acid, stir at 120℃ for 3 h, and then filter, wash, and dry) and 0.75 mmol of ammonium thiocyanate and add them sequentially to the precursor colloidal solution obtained in step (1). Continue to stir magnetically for 20 h until the solution changes from a carbon nanotube suspension to a uniform black solution. In the early stage of stirring, sonication was performed every 1 h while stirring. The sonication time was 0.5 h once, and the total sonication time was 2 h to form a stable precursor reaction solution.

[0049] Step (3): 100 mL of the precursor reaction solution obtained in step (2) was loaded into a high-pressure reactor and subjected to a hydrothermal reaction at a temperature of 170 °C for 36 h. The solid-liquid mixture obtained after the hydrothermal reaction was centrifuged, washed, and freeze-dried (freezing temperature -52 °C for 72 h) to obtain the novel tin dioxide / tin disulfide@carbon composite anode material.

[0050] In this embodiment, the tin dioxide and tin disulfide particles prepared have a diameter of 2.5–3.2 nm, and a heterojunction interface is formed between the crystals. The tin dioxide / tin disulfide heterojunction quantum dots are uniformly dispersed in the carbon nanotube wall.

[0051] Following the method of Example 1, the novel tin dioxide / tin disulfide@carbon composite anode material prepared in this example was used as the working electrode in a coin cell for electrochemical performance testing. As a lithium-ion battery anode material, its discharge specific capacity reached 1398.3 mAh / g after 100 cycles at a current density of 0.1 A / g; as a sodium-ion battery anode material, its discharge specific capacity reached 522.8 mAh / g after 100 cycles at a current density of 0.1 A / g.

[0052] Example 3: A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0053] Step (1): Measure 2.00 mmol SnSO4, 150 μL hydrazine hydrate and 200 μL NH3·H2O (25-28%), dissolve them in 100 mL of a mixture of anhydrous ethanol and deionized water (water and anhydrous ethanol volume ratio of 1:1), stir at room temperature for 24 h to form a homogeneous precursor colloidal solution.

[0054] Step (2): Weigh 300 mg of polyaniline, 120 mg of polypyrrole and 2.00 mmol of L-cysteine ​​and add them sequentially to the precursor colloidal solution obtained in step (1). Continue to stir magnetically for 24 h until dissolved and with a certain viscosity. In the early stage of stirring, sonicate every 1 h while stirring. Each sonication lasts for 0.5 h, and the total sonication time is 3 h to form a stable precursor reaction solution.

[0055] Step (3): 100 mL of the precursor reaction solution obtained in step (2) was loaded into a high-pressure reactor and subjected to hydrothermal reaction at a temperature of 200 °C for 24 h. The resulting solid-liquid mixture was centrifuged, washed, dried, and vacuum dried (at a temperature of 80 °C for 12 h) to obtain the novel tin dioxide / tin disulfide@carbon composite anode material.

[0056] In this embodiment, the tin dioxide and tin disulfide particles prepared have a diameter of 2.6–3.4 nm, forming a heterojunction interface between the crystals. The tin dioxide / tin disulfide heterojunction quantum dots are uniformly dispersed on the conductive polymer. The novel tin dioxide / tin disulfide@carbon composite anode material prepared in this embodiment was used as the working electrode in a coin cell for electrochemical performance testing. As a lithium-ion battery anode material, its discharge specific capacity reached 1056.5 mAh / g after 100 cycles at a current density of 0.1 A / g; as a sodium-ion battery anode material, its discharge specific capacity reached 507.8 mAh / g after 100 cycles at a current density of 0.1 A / g.

[0057] Example 4: A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0058] Step (1): Measure 0.60 mmol Sn(CH3COO)2 and 1.80 mmol polyethylene glycol PEG and dissolve them in 100 mL of a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of water to anhydrous ethanol is 1:1). Stir at room temperature for 10 h to form a homogeneous precursor colloidal solution.

[0059] Step (2): Weigh 23.7 mg of biochar, 1.20 mmol of thiourea and 1.20 mmol of sodium thiosulfate and add them to the precursor solution obtained in step (1) in sequence. Continue stirring for 10 h until the solution changes from a biochar suspension to a uniform black solution. In the early stage of stirring, sonicate every 1 h while stirring. Each sonication lasts for 0.5 h, and the total sonication time is 2 h to form a stable precursor reaction solution.

[0060] Step (3): 100 mL of the precursor reaction solution obtained in step (2) was loaded into a high-pressure reactor and subjected to hydrothermal reaction at 160 °C for 30 h. The resulting solid-liquid mixture was centrifuged, washed, dried, and vacuum dried (at 80 °C for 12 h) to obtain the novel tin dioxide / tin disulfide@carbon composite anode material.

[0061] The tin dioxide and tin disulfide particles prepared in this embodiment have a diameter of 2.6–3.8 nm, and the tin dioxide / tin disulfide heterojunction quantum dots are uniformly dispersed on biochar. The novel tin dioxide / tin disulfide@carbon composite anode material prepared in this embodiment was used as the working electrode in a coin cell for electrochemical performance testing. As a lithium-ion battery anode material, its discharge specific capacity reached 1053.3 mAh / g after 100 cycles at a current density of 0.1 A / g; as a sodium-ion battery anode material, its discharge specific capacity reached 501.7 mAh / g after 100 cycles at a current density of 0.1 A / g.

[0062] Example 5: A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0063] Step (1): Measure 1.20 mmol SnCl2, 1.20 mmol SnCl4 and 260 μL hydrazine hydrate and dissolve them in 100 mL of a mixture of anhydrous ethanol and deionized water (the volume ratio of water to anhydrous ethanol is 1:1). Stir at room temperature for 30 h to form a homogeneous precursor colloidal solution.

[0064] Step (2): Measure 3.0 mL of graphene dispersion (5 mg / mL), 15 mg of activated multi-walled carbon nanotubes (commercially purchased multi-walled carbon nanotubes were activated before use, and the activation method was the same as in Example 2), 2.40 mmol of thiourea and 2.40 mmol of ammonium thiocyanate and add them sequentially to the precursor colloidal solution obtained in step (1). Continue to stir magnetically for 15 h until the solution changes from a brown suspension to a uniform black solution. In the early stage of stirring, sonicate every 1 h while stirring. The sonication time is 0.5 h once, and the total sonication time is 3 h to form a stable precursor reaction solution.

[0065] Step (3): 104 mL of the precursor reaction solution obtained in step (2) was loaded into a high-pressure reactor and subjected to a hydrothermal reaction at a temperature of 150 °C for 28 h. The resulting solid-liquid mixture was centrifuged, washed, and freeze-dried (freezing temperature -52 °C for 72 h) to obtain the novel tin dioxide / tin disulfide@carbon composite anode material.

[0066] In this embodiment, the tin dioxide and tin disulfide particles prepared have a diameter of 2.5–3.2 nm, and the heterojunction quantum dots have a particle size of 5.2–5.8 nm. The tin dioxide / tin disulfide heterojunction quantum dots are uniformly dispersed in the graphene sheets and carbon nanotube walls. The novel tin dioxide / tin disulfide@carbon composite anode material prepared in this embodiment was used as the working electrode in a coin cell for electrochemical performance testing. As a lithium-ion battery anode material, its discharge specific capacity reaches 1212.9 mAh / g after 100 cycles at a current density of 0.1 A / g; as a sodium-ion battery anode material, its discharge specific capacity reaches 519.2 mAh / g after 100 cycles at a current density of 0.1 A / g.

[0067] Comparative Example 1: A method for preparing a tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0068] The material was prepared according to Example 1, except that water was used as the solvent in the synthesis process. Compared with Example 1, the XRD pattern only showed the characteristic diffraction peaks of tin dioxide, and the TEM pattern showed a very small number of tin disulfide lattice fringes. The diameters of the large amount of tin dioxide and the very small number of tin disulfide particles were 2.3–3.6 nm, and there were no heterojunction interfaces between the crystals. The tin dioxide / tin disulfide@carbon composite anode material prepared in this example was used as the working electrode in a coin cell for electrochemical performance testing. Rate testing results showed that as a lithium-ion battery anode material, its discharge specific capacity after 100 cycles at a current density of 0.1 A / g was only 847.4 mAh / g; as a sodium-ion battery anode material, its discharge specific capacity after 100 cycles at a current density of 0.1 A / g was only 362.8 mAh / g.

[0069] Comparative Example 2: A method for preparing a tin dioxide / tin disulfide@carbon composite anode material, comprising the following steps:

[0070] The material was prepared according to Example 2, except that positively charged amination multi-walled carbon nanotubes were used in the synthesis process (commercially available multi-walled carbon nanotubes were activated before use; the activating agent was octadecylamine, the activation temperature was 90°C, the activation time was 4 hours, and the activation method was the same as in Example 2). Compared to Example 2, the overall particle size was larger, with tin dioxide particles having a diameter of 30–35 nm and tin disulfide particles having a diameter of 40–50 nm. The tin dioxide particles were attached to hexagonal tin disulfide sheets, stacking to form tin dioxide / tin disulfide heterojunctions, with a very small number interleaved with carbon nanotubes. The tin dioxide / tin disulfide@carbon composite anode material prepared in this example was used as the working electrode to assemble coin cells for electrochemical performance testing. As a negative electrode material for lithium-ion batteries, its discharge specific capacity is only 562.3 mAh / g after 100 cycles at a current density of 0.1 A / g, and its discharge specific capacity is only 185.8 mAh / g. As a negative electrode material for sodium-ion batteries, its discharge specific capacity is only 394.3 mAh / g after 100 cycles at a current density of 0.1 A / g.

[0071] As can be seen from Examples 1-5 and Comparative Examples 1-2, the key point of the preparation method of the novel tin dioxide / tin disulfide@carbon composite anode material of the present invention is that, taking SnCl2 as an example, in the initial stage, Sn... 2+Intermediates (Sn(OH)2 and Sn(C2H5O)2) are generated through hydrolysis and alcoholysis, which restrict crystal growth under the regulation of additives. During ultrasonic-assisted stirring, the negative charges or oxygen-containing groups on the surface of the carbon material are bonded together by CO-Sn through electrostatic attraction or dehydration condensation reaction, further dispersing and restricting crystal growth. This method yields tin dioxide / tin disulfide heterojunction quantum dots after hydrothermal treatment. The quantum dots constructed by this method can effectively reduce the absolute volume change of the material while improving its structural stability. The formed tin dioxide / tin disulfide heterojunction can induce an internal electric field through interfacial interactions, accelerating charge transfer and enhancing the conductivity of the material. The combination of the quantum dot effect and the tin-based heterojunction material forms a synergistic effect of heterojunction quantum dots, resulting in excellent electrochemical performance of the electrode material.

[0072] The specific embodiments of the present invention described above are merely illustrative of several implementations and are described in detail for ease of understanding, but they do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a novel tin dioxide / tin disulfide@carbon composite anode material, the specific operation of which is as follows: Step (1): Dissolve the tin source and additives in a mixed solvent of organic alcohol and deionized water, and stir under controlled temperature until uniformly dispersed to form a tin quantum dot precursor colloidal solution; Step (2): Add the carbon source and sulfur source to the precursor solution obtained in step (1) and stir continuously for 6 to 30 h. During the stirring process, add ultrasonic assistance to form a precursor reaction solution. Step (3): The precursor reaction solution obtained in step (2) is loaded into a high-pressure reactor and subjected to hydrothermal reaction at 120~300℃ for 6~36 h. After the reaction is completed, the resulting solid-liquid mixture is centrifuged, washed and dried to obtain the novel tin dioxide / tin disulfide@carbon composite anode material. The carbon source is a carbon material with a negatively charged surface; In step (2), the specific conditions for ultrasonic assistance are: ultrasonication is performed at intervals while stirring, each time for 0.5 hours, and the total ultrasonic time is 2 to 3 hours. The mixed solvent of the organic alcohol and deionized water is an anhydrous ethanol and deionized water mixed solvent with a volume ratio of 1:

1. The additive is one or more of the following: N2H4·H2O, NH3·H2O, NaOH, NaHCO3, Na2CO3, KOH, KHCO3, K2CO3, C3H8O3, EG, VA, IPA, PEG, and PVA.

2. The preparation method according to claim 1, characterized in that, In step (1), the tin source is SnCl2, SnCl4, SnSO4, Na2SnO3, K2SnO3, Sn(CH3COO)2, SnC2O4, C 16 H 30 O4Sn, C 12 H 27 One or more of Sn, wherein the molar ratio of the additive to the tin source is (2~8):

1.

3. The preparation method according to claim 1, characterized in that, In step (1), the molar concentration of tin source in the tin quantum dot precursor colloidal solution is 6~24 mmol / L, the stirring temperature is 5~40℃, and the stirring and dispersion time is 10~30 h.

4. The preparation method according to claim 3, characterized in that, In step (2), the carbon source is one or more of the following: carbon nanotubes with negative surface charge, graphene, anionic polymer pyrolytic carbon, biochar, and activated carbon; the sulfur source is one or more of the following: thiourea, L-cysteine, sodium thiosulfate, sodium sulfide, ammonium thiocyanate, thioacetamide, ammonium sulfide, sodium sulfide, potassium sulfide, potassium thiocyanate, and sodium thiocyanate.

5. The preparation method according to claim 1, characterized in that, The mass ratio of the carbon source to the tin source is 1:(1~20), and in step (2), the molar ratio of the sulfur source to the tin source is (0.5~4):

1.

6. The preparation method according to claim 1, characterized in that, In step (3), the hydrothermal reaction is carried out at a temperature of 150-200°C and a reaction time of 20-36 h.

7. The application of the novel tin dioxide / tin disulfide@carbon composite anode material obtained by the preparation method according to any one of claims 1-6 in the preparation of battery anode materials.

8. The application according to claim 7, characterized in that, The battery anode material is a lithium-ion battery anode material, a sodium-ion battery anode material, a potassium-ion battery anode material, or a lithium / sodium-sulfur battery anode material.